Efektivitas Telehealth dalam Meningkatkan Kualitas Asuhan Keperawatan: Literature Review Tahun 2020-2026 - Teten Rustendi; Nana Suryana; Nur Umi Aminatus Solichah; Euis Nurhayati; Meli Marlina (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Telehealth is a technology-based healthcare innovation that enables remote nursing care delivery through digital communication. In recent years, telehealth has increasingly been adopted as an effort to improve access and quality of nursing services. This study aims to analyze the effectiveness of telehealth in improving the quality of nursing care using a literature review approach. The method used is a literature review with secondary data sources obtained from Google Scholar, PubMed, and ScienceDirect covering publications from 2020 to 2026. Selected articles were analyzed using descriptive narrative synthesis based on predefined inclusion and exclusion criteria. The results show that telehealth is effective in improving nursing care quality through better access to healthcare services, improved nurse–patient communication, enhanced patient safety, increased patient satisfaction, and continuity of care. In addition, telehealth supports continuous patient monitoring and assists nurses in clinical decision-making. However, several challenges remain, including technological infrastructure limitations and healthcare professionals’ digital literacy. In conclusion, telehealth plays an important role in improving nursing care quality and has strong potential to become a key model of nursing service in the digital era.